The nested graft acts by inducing the process of de‐senescence of the fibroblasts in chronic venous ulcers. Issue 6 (19th March 2015) - Gualdi, Giulio; Crotti, Silvia; Monari, Paola; Calzavara‐Pinton, Piergiacomo; Vitali, Massimiliano; Baronio, Manuela; Lougaris, Vassilios
Abstract: Senescent fibroblasts, which are present in chronic ulcers, are the reason for the wound becoming chronic. In this study, we introduce full‐thickness micro skin grafts in the ulcer, a surgical technique known as a 'nested graft', which gave encouraging results leading to complete wound healing in all patients. The assessment of fibroblast cultures taken from the wound before and after treatment and comparison with fibroblasts from healthy skin showed that the fibroblasts taken from the ulcer after the nested graft treatment acquire morpho‐functional characteristics overlapping those of fibroblasts from healthy skin. This surgical approach is, therefore, able to lead to the healing of chronic ulcers through the de‐senescence of the fibroblasts.